Exercise-based pre-habilitation is feasible and effective in radical cystectomy pathways—secondary results from a randomized controlled trial - Jensen, Bente Thoft; Laustsen, Sussie; Jensen, Jørgen Bjerggaard; Borre, Michael; Petersen, Annemette Krintel (Supportive care in cancer, 2016)
Background Physical exercises offer a variety of health benefits to cancer survivors during and post-treatment. However, exercise-based pre-habilitation is not well reported in major uro-oncology surgery. The aim of this study was to investigate the feasibility, the adherence, and the efficacy of a short-term physical pre-habilitation program to patients with invasive bladder cancer awaiting radical cystectomy (RC). Methods A parent prospective randomized controlled clinical trial investigated efficacy of a multidisciplinary rehabilitation program on length of stay following RC. A total of 107 patients were included in the intension-to-treat population revealing 50 patients in the intervention group and 57 patients in the standard group. Pre-operatively, the intervention group was instructed to a standardized exercise program consisting of both muscle strength exercises and endurance training. The number of training sessions and exercise repetitions was patient-reported. Feasibility was expressed as adherence to the program and efficacy as the differences in muscle power within and between treatment groups at time for surgery. Results A total of 66 % (95 % confidence interval (CI) 51; 78) adhered more than 75 % of the recommended progressive standardized exercise program. In the intervention group, a significant improvement in muscle power of 18 % ( p < 0.002) was found at time for surgery. Moreover, muscle power was significantly improved compared to that in the standard group with 0.3 W/kg (95 % CI 0.08; 0.5 %) ( p < 0.006). Adherence was not associated with pre-operative BMI, nutritional risk, comorbidity, pain, gender, or age. Conclusion In patients awaiting RC, a short-term exercise-based pre-habilitation intervention is feasible and effective and should be considered in future survivorship strategies.